Additive manufacturing of Al2O3 with engineered interlayers and high toughness through multi-material co-extrusion. (1st March 2023) - Zhou, Shitong; Cai, Qiaosong; Tirichenko, Iuliia S; Vilchez, Victoria; Gavalda-Diaz, Oriol; Bouville, Florian; Saiz, Eduardo
Abstract: The additive manufacturing of ceramic composites with tailored microstructures is still challenging and time-consuming. However, there is great interest as it may enable the implementation of novel materials architectures following computer designs. In this work, we demonstrate a straightforward method to obtain ceramics with a network of continuous weak interlayers designed to increase fracture resistance using alumina as a model system. This is achieved by combining direct ink writing with the coextrusion of multi-material pastes with carefully matched rheology based on thermally reversible hydrogels and inorganic powders. The printed Al2 O3 bars with and without weak interlayers exhibit strengths ranging between 180 and 360 MPa and K IC ∼ 3 MPa∙m 1/2 . The introduction of weak interlayers using different raster patterns, such as length wise and Bouligand alignments can be used to direct crack propagation and promote gradual failure. The result is an improvement in the fracture energy up to 230 J/m 2 and K J up to 9 MPa · m 1/2 . These results suggest the potential of manufacturing ceramics with enhanced mechanical properties by using robocasting with multi-material inks to engineer complex interlayer networks. Graphical abstract: Image, graphical abstract